2003
DOI: 10.1159/000071945
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Vascular Responses to Changes in Carbon Dioxide Tension in Term and Preterm Infants with Apnea

Abstract: Carbon dioxide (CO2) plays important roles in regulating both respiratory drive and cerebral blood flow. These effects are mediated, in part, by activity of the sympathetic nervous system. We hypothesized that the presence of acute life-threatening events or apnea in term or preterm infants, respectively, would serve as a marker for immaturity of cerebral autonomic innervation and that such infants would display a reduced cerebral vascular response to elevated pCO2. Therefore, we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Previous studies have shown up to a 200% increase in CBF as PCO 2 increases to values similar to case 6 (PCO 2 , 54). [18][19][20][21][22][23][24][25][26] We believe that the global hyperperfusion in case 6 is a result of hypercapnia rather than anoxia.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown up to a 200% increase in CBF as PCO 2 increases to values similar to case 6 (PCO 2 , 54). [18][19][20][21][22][23][24][25][26] We believe that the global hyperperfusion in case 6 is a result of hypercapnia rather than anoxia.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the rapid decrease of pCO 2 and increase of pO 2 occurring during the first minutes of life could play a role in the reduction of cerebral blood flow observed in the neonates in the first hours of life4. Increase in arterial pCO 2 causes cerebral vasodilatation18, 19. Hypoxemia is also a strong vasodilator, while an increase in oxygen tension correlates with decreased cerebral blood flow velocities20, 21.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,8 Previous human studies demonstrated up to a 200% increase in CBF as pCO 2 was raised experimentally. 3,4,[8][9][10][11][12][13]35 However, a blunted hypercapnic response in elderly subjects has been shown during experimentally induced hypercapnia. 11,36,[40][41][42][43][44] The impaired vasodilatory response with aging may be related to sclerotic changes in the arterial wall or baseline oxyhemoglobin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,8 Even small increases in the partial pressure of CO 2 (pCO 2 ) on the order of 5 to 6 mm Hg are capable of generating appreciable changes on perfusion imaging. 3,4,[7][8][9][10][11][12][13] Techniques such as transcranial Doppler, nuclear medicine positronemission tomography (PET) and single-photon emission CT, angiography, phase-contrast MR imaging, and arterial spinlabeled (ASL) MR perfusion have been used to evaluate the experimental hypercapnic effect on cerebral perfusion. 4,7,[11][12][13][14][15][16][17][18][19][20][21][22][23] It is not uncommon that hospitalized patients can have marked increases in pCO 2 in excess of 30 mm Hg from baseline, both on an acute or on a chronic basis.…”
mentioning
confidence: 99%